KESESUAIAN MATERI PERKULIAHAN PENDIDIKAN TEKNIK BANGUNAN TERHADAP KOMPETENSI YANG DIPERLUKAN DALAM ASISTENSI MENGAJAR DI SEKOLAH MENENGAH KEJURUAN - Shafa Nathaniela Adhinaya; Sutrisno (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Teaching Assistance (AM) is a form of the Merdeka Belajar Kampus Merdeka (MBKM) program that provides pre-service teacher students with direct teaching experience in Vocational High Schools (SMK). This study aims to: (1) identify the competencies required by students in the AM program; (2) analyze the level of alignment between Building Engineering Education (PTB) course materials and those competencies; and (3) test the significance of that alignment using the Chi-Square test. The study used a quantitative, ex post facto non-experimental descriptive approach supported by qualitative data from student essays. Data were collected through a 1–4 Likert-scale questionnaire distributed to 76 PTB students from the 2022 cohort who had completed the AM program. The results show that of 30 materials tested, 19 fell into the highly needed category, particularly in the professional aspect (Basic Technical Drawing and Cost Estimation) and the pedagogical aspect (Teaching Modules, Lesson Plans, and Learning Outcomes/Objectives). The alignment level between PTB materials and AM competencies showed that 37% of materials were highly aligned, 47% aligned, and 17% less aligned. The Chi-Square test revealed that 19 of 30 materials showed a significant difference (p < 0.05) between course content and AM needs, particularly in practical pedagogical materials such as classroom management, teaching-module preparation, and lesson planning. This study recommends adjusting the PTB curriculum to be more practice-oriented, integrated with industry needs, and to provide authentic teaching experience earlier in the study program.